2005
DOI: 10.1139/s04-066
|View full text |Cite
|
Sign up to set email alerts
|

By-product formation during ultraviolet disinfection of a pretreated surface water

Abstract: A low-pressure (LP-UV) and medium-pressure UV lamp (MP-UV) were compared for the formation of nitrite, assimilable organic carbon (AOC), and genotoxicity using pretreated surface water in a bench UV unit. The results have been compared with the by-products formed in pretreated surface water using a pilot unit equipped with four mediumpressure lamps identical to the one used in the bench unit. It was found that although significant nitrite formation occurred in the MP-UV bench tests, it remained well below the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, it was reported that nitrite formation rarely exceeded 100 µg L −1 , showing that nitrite levels were in compliance with regulations when low UV fluences were employed. [19,21] Hydrogen peroxide was shown to increase nitrite formation during polychromatic UV irradiation of drinking water. [22] There is a lack of information on the AOT treatment of secondary effluent in two aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported that nitrite formation rarely exceeded 100 µg L −1 , showing that nitrite levels were in compliance with regulations when low UV fluences were employed. [19,21] Hydrogen peroxide was shown to increase nitrite formation during polychromatic UV irradiation of drinking water. [22] There is a lack of information on the AOT treatment of secondary effluent in two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…[2,5,6,8,14,19,22] There is insufficient information on the impacts observed from practical field application of the AOT to water and wastewater treatment. The objectives of this study were to test the field applicability of AOT at a pilot scale to a secondary effluent from an activated sludge process without nutrient removal, and to investigate the effect of AOT on inactivation and on changes in nitrate-nitrite concentrations in the product water under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Choi, et.al. [230] and IJepaar, et al [231] found that the use of MP mercury lamps did increase AOC in bench- and pilot-scale studies, and in actual drinking water facilities; LP mercury lamps did not appreciably increase AOC concentration. The increase in AOC and possible regrowth of microorganisms downstream of the UV system are critical considerations for membrane systems using MP-lamp, UV radiation for pretreatment disinfection.…”
Section: Techniques To Address Membrane Biofoulingmentioning
confidence: 99%
“…Some articles discovered increased AOC after UV irradiation and showed that the bioavailability of organic matter could be enhanced by UV as the generation of oxygen-rich compounds as well as the increase of low molecular weight compounds such as amino acids and carbohydrates (Shaw et al, 2000;Thayanukul et al, 2013). Higher UV irradiation doses could lead to elevated AOC concentrations (Ijpelaar et al, 2005). Nevertheless, others detected no obvious impact (Polanska et al, 2005) or even declined AOC levels (Lehtola et al, 2003).…”
Section: Disinfectionmentioning
confidence: 99%